2013
DOI: 10.1111/cid.12030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Implant Angulation on Attachment Retention in Mandibular Two‐Implant Overdentures: A Clinical Study

Abstract: Increased interimplant angulation appears to have higher impact on the retention of LA than of RA attachments. The effect of larger interimplant angulation on the loss of attachment retention and its clinical implications should be further assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 14 publications
0
39
0
Order By: Relevance
“…Other short-term clinical research observed only a negative impact of higher sagittal inter-implant angles on the retention (Jabbour et al, 2014). The parallel implant position should reduce the number of visits, which are time-consuming for both patient and clinician.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Other short-term clinical research observed only a negative impact of higher sagittal inter-implant angles on the retention (Jabbour et al, 2014). The parallel implant position should reduce the number of visits, which are time-consuming for both patient and clinician.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, other studies found no effect of the inter-implant distance on both the quality of the dentures and the patient satisfaction (Alfadda, Al Amri, Al-Ohali, Al-Hakami, & Al-Madhi, 2017). Based on in vitro and in vivo research, the effect of inter-implant angulation on retention and wear of a stud retained 2IOD is inconclusive (ELsyad, Hatem, Shawky, & Emera, 2018;Jabbour et al, 2014;Kobayashi et al, 2014;Kurtulus & Gurbulak, 2018;Stephens, di Vitale, O'Sullivan, & McDonald, 2014).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, Locators have a low profile and can be used with inadequate interridge space to reduce denture base fracture . In addition, they can compensate for implant angulation . The manufacturers recommend the use of conventional Locator inserts (with double frictional flanges) where interimplant angles are in the range of 0° to 20°.…”
mentioning
confidence: 99%
“…The manufacturers recommend the use of conventional Locator inserts (with double frictional flanges) where interimplant angles are in the range of 0° to 20°. Extended range inserts (with external frictional flange only) are recommended for use where interimplant angles exceed 20° . However, Locator inserts are not resistant to wear and show reduced retention clinically compared to ball attachments…”
mentioning
confidence: 99%